Correlation between CMR and chest CT in assessment of constrictive pericarditis. - Hadji Nikolova Alchinova, Natasha; Lazareska, Menka; Panchevska, Ivana; Ilievski, Mitko; Nikolova, Sonja; Pashoska, Milkica; Stojkoski, Aleksandar; Aliji, Vjollca; Stamenkovski, Nikola (My University, 2023)
Description of Clinical Presentation A 35-year-old adult presented to the cardiology department with shortness of breath, coughing, and fatigue. He had a history of recurrent colds with high fever, but their recent cold led to worsening symptoms. Tests revealed atrial fibrillation with a heart rate of 150 bpm, enlarged atria, and reduced systolic function. Laboratory results showed thrombocytopenia, elevated GGT, and high bilirubin, with no elevated Troponin levels. CMR showed systemic volume overload, with passive liver congestion and left pleural effusion, no pericardial effusion, but thickening with dimensions of 4,6mm. SSFP sequences showed left and right ventricle hypokinesia with impaired diastolic filling, severe diastolic septal bounce and abnormal contour of left lateral wall which was akinetic. The T2-STIR sequence showed hypersignal intensity in the basal anterolateral and inferolateral segments, distributed within the subepicardial and mid-wall regions. Additionally, focal pericardial involvement was observed in these segments, along with two central hypo signal lesions that showed identical signal characteristics across all sequences. On delayed enhancement PSIR sequences, there was increased signal intensity in the specific areas on the T2-STIR sequence, suggesting gadolinium accumulation and in the mid and apical inferior and inferolateral segments with subepicardial distribution. There was pericardial enhancement dominantly at the basal ventricular segments, along with focal pericardial enhancement at the left apex also featuring a central hypo signal lesion. The patient underwent a native chest CT examination, revealing circumferential thickening of the pericardium with linear diffuse calcifications. This finding was correlated with the MRI results, indicating a state of subacute to chronic inflammatory/fibrotic constrictive pericarditis with constriction throughout the entire heart with concomitant myocarditis changes dominantly at the left lateral wall. Diagnostic Techniques and Their Most Important Findings Cardiac MRI is a valuable tool for diagnosis of pericardial constriction where the ventricles may appear compressed or have a "square root sign" appearance, reflecting impaired ventricular filling during diastole. T1 and T2 mapping, can provide insights into the tissue characteristics of the pericardium and myocardium. These techniques can help differentiate between pericardial and myocardial involvement and assess the degree of fibrosis. Cardiac MRI can assess respirophasic variation in ventricular filling, which is a hallmark feature of pericardial constriction. During inspiration, there may be an exaggerated increase in ventricular filling due to reduced compliance of the constricted pericardium. Learning Points from this Case Pericardial constriction, characterized by impaired diastolic filling due to thickened, fibrotic, and/or calcified pericardium, can be a diagnostic challenge, often requiring the use of multiple imaging modalities which within this case with the correlation between TTE, CMR and CT scan a noninvasive diagnosis can be made.
Oral presentation of an accepted and published case study at the Global CMR Conference 2024, January 25- 27, London, UK
Keywords: Calcification; Pericardial Constriction; Myocarditis